Updated Italian checklist of Tenuipalpidae with description of a new species and new worldwide records of the genus Cenopalpus (Pritchard et Baker) - De Giosa, Marcello; Ochoa, Ronald; Castro, Elizeu B. [UNESP]; Simoni, Sauro; Glik, Tobias; Tassi, Aline D.; de Lillo, Enrico (Taylor & Francis, 2024)
The family Tenuipalpidae includes agricultural pests that have garnered extensive attention from the global research community. Despite the economic importance of tenuipalpids, due to their ecology and global trade of the infested plants, there has not been any corresponding and comprehensive research on these mites in Italy in recent decades. This study aimed to determine the species composition of tenuipalpid mites in Italy, update the Italian checklist for the taxon, and include new records and host plant associations of the genera Brevipalpus Donnadieu and Cenopalpus Pritchard and Baker worldwide. The study found several new records of tenuipalpid species in Italy, including four Cenopalpus and two Brevipalpus species. Additionally, one new species Cenopalpus ulmifolius De Giosa, Ochoa et de Lillo was added to the list. The research also incorporated new records of Cenopalpus species in different countries and several new host plant associations and the description of novel taxonomic characters were present for the Cenopalpus species studied during this work, since they were the most abundant tenuipalpid collected in the sampled areas. The study’s findings are crucial for developing effective management for tenuipalpid mites, understanding the fauna composition, and constructing preparedness strategies for quarantine purposes.
Keywords: Acari; Brevipalpus; flat mites; interceptions; Mediterranean area; Pentamerismus; phytophagous pests; Tenuipalpus taxonomy; Trombidiformes